Analysis Of Immunomodulator Drug Prescribing Practices In Dermatology: A Study On Trends, Dosage, And Formularies In A Tertiary Care Teaching Hospital - Ahmed, Ashwak; Navaluri, Ramakrishna (Journal of Neonatal Surgery, 2025)
This research aims to examine immunomodulator drugs (IMDs) prescribing patterns in a dermatology outpatient department of one of the Tertiary Care Teaching Hospitals. It targets the demographic distribution, prevalence of dermatological conditions and IMD trend distributions especially on the corticosteroids. The study noted that more than a half of prescribed drugs were IMDs, brand prescriptions (62%) were given preferably to generic names (38%). Most prescriptions used recommended doses, and there was equilibrium in the local and systemic administration route. Most common corticosteroids that were prescribed were prednisolone and betamethasone and most used super-potent topical steroids. Also, there was evidence on how the Hospital Drug Formulary (HDF) was used and 51 percent of the IMDs were ordered using the formulary showing that access to medication would be improved. In general, the research reveals that IMD prescription still needs to be continuously monitored to maximize the effect of treatment and enhance the use of drugs and support patients better in dermatological practices